Reconstruction algorithm for tunneling ionization with a perturbation for the time-domain observation of an electric-field - Cho, Wosik (Sci Rep, 2021)
We present a reconstruction algorithm developed for the temporal characterization method called tunneling ionization with a perturbation for the time-domain observation of an electric field (TIPTOE). The reconstruction algorithm considers the high-order contribution of an additional laser pulse to ionization, enabling the use of an intense additional laser pulse. Therefore, the signal-to-noise ratio of the TIPTOE measurement is improved by at least one order of magnitude compared to the first-order approximation. In addition, the high-order contribution provides additional information regarding the pulse envelope. The reconstruction algorithm was tested with ionization yields obtained by solving the time-dependent Schrödinger equation. The optimal conditions for accurate reconstruction were analyzed. The reconstruction algorithm was also tested using experimental data obtained using few-cycle laser pulses. The reconstructed pulses obtained under different dispersion conditions exhibited good consistency. These results confirm the validity and accuracy of the reconstruction process.